Emiliano Zapata: pensamiento revolucionario - Rosales García, Juana (2016)
In the study of the emancipating ideas of America, the imprint and evaluation of the thought of Emiliano Zapata (1879-1919) occupies a prominent place. To highlight some aspects of the thought of the leader of the first popular movement claim against the roots of social injustice during the last century, and who fought for the dignity of the exploited agricultural masses against native landlords and foreign capitalists, is a main objective of this work. I also address the Zapatista agrarian policy and the place it occupied in the Plan of Ayala, and the importance Zapata granted the ethical- political relationship.